CORRELATION BETWEEN PLASMA THYROID HORMONES AND LIVER ENZYMES LEVEL IN THYROTOXIC CASES AND CONTROLS IN HAZARA DIVISION - Khan, Tariq Mehmood; Malik, Saqib; Diju, Inayat Ullah (Journal of Ayub Medical College Abbottabad, 2010)
Background: Thyrotoxicosis is defined as increased synthesis and secretion of thyroid hormones; when associated with defused goitre it is known as grave’s disease. Hepatic changes in thyrotoxiosis are fatty changes, cirrhosis and centrilobular necrosis, resulting in elevated serum levels of liver specific enzymes ALT, AST and ALK. Objective of the study was to determine a correlation between plasma levels of 3 liver enzymes, and thyroid hormones in thyrotoxic cases, and matched controls in Hazara Division. Methods: This study was conducted at Ayub Teaching Hospital Abbottabad from 1st July 2004 to 30th June 2007. The controls were selected from staff and students of Ayub Medial College Abbottabad. Fifty cases of thyrotoxicosis and 50 controls were included in this study by convenience sampling. Their thyroid profile for T3, T4, TSH and liver enzymes profile for ALT, AST, ALK were determined and analysed for a correlation. Results: Mean T3 of cases was 5.23±1.95 and of controls 1.95±0.35. Mean T4 of case was 248.88±62.75, and of controls was 113.40±19.01. Mean TSH of cases was 0.07±0.25 and that of controls was 2.24±0.80. Mean ALT of cases was 38.78±4.96 while that of controls was 23.98±5.27. Mean AST of cases was 39.76±5.05 and of controls was 26.52±4.49. Mean ALK of cases was 299.68±22.32 and of controls was 155.10±37.07. Conclusion: Although liver enzymes levels were slightly elevated in many thyrotoxic cases, no significant correlation emerged between any of the thyroid hormones and any of the liver enzymes, either in cases or controls. Keywords: Thyrotoxiosis, Liver enzymes, Grave’s disease, Hyperthyroidism